Role of leadership behaviours in mitigating physician burnout in Pakistan - Moeen ud Din, Khawaja; Asif, Muhammad Ahsan; Iqbal, Minahil (Journal of the Pakistan Medical Association, 2024)
Dear Sir / Madam. Respectable Editor, Physician burnout is the reality of the modern-day world that influence the quality of patient care, physician turnover, and long-term patient satisfaction. Several components become a part of this unfortunate phenomenon which includes emotional exhaustion and decreased level of productivity. These features lead to a sense of negativity and depersonalization from the reality which in turn results in the overall reduced sense of personal accomplishments and efficacy. For the most part these constituents effect the working environment in the hospital settings in way that leads to deleterious impact on work healthcare output.1 Worldwide physician burnout has reached global epidemic levels, with recent studies conducted in local hospital settings in Pakistan showing a prevalence of high burnout in 13.5% and moderate level of burnout in 62.2% among the physicians. An eye opening data of 33% doctors desired to quit their jobs.2 Current scenarios after the post-pandemic era and now the hazardous economic destabilization of Pakistan is playing a role of catalyst for the dissatisfaction, mental and physical anguish among the physicians hence leading to an increased burnout. In relation to this matter, the most important factor playing a significant role in amelioration of this grim situation is the role of leadership staff. A recent study has identified that the leadership behaviour ratings of physicians’ supervisors are negatively associated with burnout and are positively linked with a sense of professional fulfilment. In the same study, they have rightly pointed out that physicians are more likely to depart from a place where they are not acknowledged enough.3 Another similar study conducted by James et al. using the Full Range of Leadership Model (FRLM) has successfully reported that transformational leadership behaviours that include idealized influence, and individualized consideration cultivate a sense of higher-order values, purpose, and individualized development to achieve performance that is beyond expected from the usual scenarios.4 Keeping that in mind, the present distressing burnout situation calls for an emergent need to take immediate appropriate actions to mitigate the prevalent situation with involved and supportive leadership qualities like the provision of comprehensive support groups, a humane number of working hours, improved salary packages, de-stressing activities like sports on department level etc. to ameliorate the mental health of physicians and enhance their overall productivity.5 To conclude, physician burnout is reparable with minimum efforts in the form of improved supervision and management qualities of the leadership staff. —Continue